Menimbang Kaidah Syādz dalam Kritik Hadis: Kerangka Konseptual dan Aplikasinya pada Sanad serta Matan: Kerangka Konseptual dan Aplikasinya Pada Sanad Serta Matan - Munadi, Radhie (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2026)
In general, this study examines the shādhdh principle in ḥadīth criticism, emphasizing that assessing the validity of a report cannot rely solely on an isnād that appears sound, but must also involve detecting irregularities revealed through comparison across transmission routes (mu‘āraḍah/muqāranah) in both isnād and matn. The methodology employs an analytical–conceptual, library-based approach, tracing primary literature to map definitions, the foundations of application, and the distinctions of shādhdh in isnād and matn within the classical tradition of ḥadīth criticism and its relevance to contemporary discourse. The findings show: (1) shādhdh is understood as a narration transmitted by a trustworthy (thiqah) narrator that contradicts a stronger narration; (2) there are differences in formulation among al-Shāfiʿī, al-Ḥākim, and al-Khalīlī, yet scholars tend to privilege al-Shāfiʿī’s definition; and (3) identifying shādhdh in the isnād is carried out by compiling all chains, evaluating the reliability of narrators, and then determining maḥfūẓ versus shādhdh/marjūḥ, whereas shādhdh in the matn is established through muqāranah and by testing forms of “irregularity” such as maqlūb, mudraj, ziyādah, muḍṭarib, muṣaḥḥaf, and muḥarraf. The implications underscore the importance of comparative work across transmission lines to prevent the acceptance of reports that are “formally sound yet deviant,” while providing a methodological basis for more measured and responsible matn criticism in contemporary ḥadīth studies.